Advancing 21st-Century Skills in Early Childhood Through the Project-Based Learning Model: Evidence from Children Aged 5–6 Years - Shiddiq, Azka Arina Nur Kamila; Sutama, I Wayan; Astuti, Wuri (Universitas Pendidikan Ganesha, 2024)
The paradigm shifts of 21st century education directs children to have not only knowledge, but also skills. The skills in question include communication, critical thinking, creativity, and collaboration, known as the 4Cs. In early childhood education, it is important for teachers to use learning models that can stimulate 21st century skills, one of which is the project-based learning model. This study aims to analyze the effect of the project-based learning model on the 21st century skills of children aged 5–6 years. The subjects of the study were children in group B at a school that had implemented a project-based learning model. The research design used was Nonequivalent Control Group Design. Data collection was carried out through participatory observation using observation sheets that had been tested for reliability and construct validity. Data were analyzed using descriptive analysis and non-parametric tests. From the experimental class, the average pretest score was 41.813 and the average posttest score was 80.938, indicating an increase in 21st century skills after treatment using project-based learning. Hypothesis testing using the Mann-Whitney U Test produces a significance value of <0.001 (<0.05). It can be concluded that there is a significant influence of the project-based learning model on the 21st century skills of children aged 5–6 years. The implication of this study is to provide the latest information on the influence of project-based learning in improving 21st century skills.